A history of the use of the concept of parental alienation in the Australian family law system: contradictions, collisions and their consequences. Issue 1 (2nd January 2020) - Rathus, Zoe
ABSTRACT: This paper presents insights into the history and current deployment of the concept of parental alienation in the Australian family law system. It begins in 1989, when an article on parental alienation syndrome was first published in an Australian law journal. It then traces aspects of the socio-legal and social science research, gender politics, law reform and jurisprudence of the following 30 years, paying attention to moments of significant change. The impacts of major amendments that emphasise the desirability of post-separation shared parenting outcomes in 1996 and 2006 are specifically considered. More recently, in 2012, reforms intended to improve the family law system's response to domestic and family violence were introduced. The history reveals an irreconcilable tension between the 'benefit' of 'meaningful' post-separation parent-child relationships and the protection of children from harm. When mothers' allegations of violence in the family are disbelieved, minimised or dismissed, they are transformed from victims of abuse into perpetrators of abuse – alienators of children from their fathers. Their actions and attitudes collide with the shared parenting philosophy. This is arguably an inescapable consequence of a family law system that struggles to deal effectively with family violence in the context of a strong shared parenting regime.